The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/1574-6968.12533
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriaassociated with arbuscular mycorrhizal fungi within roots of plants growing in a soil highly contaminated with aliphatic and aromatic petroleum hydrocarbons

Abstract: Arbuscular mycorrhizal fungi (AMF) belong to phylum Glomeromycota, an early divergent fungal lineage forming symbiosis with plant roots. Many reports have documented that bacteria are intimately associated with AMF mycelia in the soil. However, the role of these bacteria remains unclear and their diversity within intraradical AMF structures has yet to be explored. We aim to assess the bacterial communities associated within intraradical propagules (vesicles and intraradical spores) harvested from roots of plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 55 publications
(77 reference statements)
1
29
1
1
Order By: Relevance
“…Recently, Iffis et al . () identified fungi belonging to Chytridiomycota , as well as bacteria belonging mainly to the genera Sphingomonas , Pseudomonas , Massilia , and Methylobacterium from vesicles and intraradical spores of AMF collected within Solidago rugosa roots growing in the extremely petroleum hydrocarbon‐polluted basin on the same site used in our study. However, the roles of the microorganisms associated with AMF and the mechanisms that govern their interactions remain poorly explored particularly in highly stressful conditions such as polluted environments.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Recently, Iffis et al . () identified fungi belonging to Chytridiomycota , as well as bacteria belonging mainly to the genera Sphingomonas , Pseudomonas , Massilia , and Methylobacterium from vesicles and intraradical spores of AMF collected within Solidago rugosa roots growing in the extremely petroleum hydrocarbon‐polluted basin on the same site used in our study. However, the roles of the microorganisms associated with AMF and the mechanisms that govern their interactions remain poorly explored particularly in highly stressful conditions such as polluted environments.…”
Section: Discussionmentioning
confidence: 68%
“…The observed AMF-associated microbial communities are in line with what was observed previously by other authors both in in vitro conditions and in agricultural soils (Hijri et al, 2002;Mirabal Alonso et al, 2008;Scheublin et al, 2010;Lecomte et al, 2011;Lace et al, 2015;Battini et al, 2016), although much larger bacterial and fungal communities were found here owing to the use of high throughput sequencing. Recently, Iffis et al (2014) identified fungi belonging to Chytridiomycota, as well as bacteria belonging mainly to the genera Sphingomonas, Pseudomonas, Massilia, and Methylobacterium from vesicles and intraradical spores of AMF collected within Solidago rugosa roots growing in the extremely petroleum hydrocarbon-polluted basin on the same site used in our study. However, the roles of the microorganisms associated with AMF and the mechanisms that govern their interactions remain poorly explored particularly in highly stressful conditions such as polluted environments.…”
Section: Associations Between Amf Spores and Microbial Communitiesmentioning
confidence: 84%
See 2 more Smart Citations
“…In addition, Welc et al (2010) reported that AMF mycelium could suppress the soil bacterial community. Furthermore, many specific bacterial taxa are highly associated with AMF as they colonize and live on the surface of the hyphae (Cruz and Ishii, 2011; Iffis et al, 2014). For example, certain Proteobacteria and Firmicutes taxa have been documented as co-existing with AMF (Bonfante and Anca, 2009; Scheublin et al, 2010; Lecomte et al, 2011).…”
Section: Introductionmentioning
confidence: 99%